Improving the Academic Supervision Ability of Elementary School Principals in Using Hybrid Supervision Model through Online Training - Yari Dwikurnaningsih; Sophia Tri Satyawati; Marinu Waruwu (STKIP Singkawang, 2025)
Supervision constraints, which are carried out face-to-face or fully online, encourage the creation of a hybrid supervision model. To be able to carry out supervision in a hybrid manner, supervisors need to be equipped with knowledge and skills to be able to apply it appropriately. The objective of this study is to improve the ability of Education supervisors to carry out hybrid academic supervision through online training. This research approach was a mixed method with school action research methods. The subjects of this study were 20 people consisting of the principal and vice principal. Data collection techniques use observation, interviews, and tests. Data analysis techniques used qualitative descriptive data analysis of Miles and Huberman models and quantitative descriptive data analysis techniques. The results showed an increase in the ability of participants after attending the training. This is proven by the increase in knowledge, skills and attitudes of trainees from pre-cycle, cycle 1 and cycle 2. In the pre-cycle stage, knowledge scores 32, skills 53, and attitudes 49. In cycle 1 the posttest results score knowledge 57, skill 75, and attitude 64. And in cycle 2 increased knowledge score 87, skill 93, and attitude 88. Based on the results of cycle 2, it can be seen that all participants have been able to achieve the established success indicator of ≥ 80. Thus, it can be concluded that online training can improve the ability of participants to apply hybrid model academic supervision.